Optimalisasi Pembiayaan Pendidikan Berbasis Kinerja untuk Peningkatan Mutu Pembelajaran di Masyarakat (Studi Kasus BOS Kinerja di SMA Kota Palangka Raya) - Mulyadi, Edi; Dewi, Wahi Sari; Sulistyaningrum, Wiwiek; Ni’mah, Istiqomah; Wuryani, Etti Dwi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study addresses the challenge of improving learning quality in senior high schools located in resource limited regions, with a specific focus on Palangka Raya City. In this context, the Performance-Based School Operational Assistance program (BOS Kinerja) serves as a strategic incentive-based funding mechanism to enhance educational outcomes. The study aims to examine the implementation of BOS Kinerja and its impact on teacher competence, student engagement, and academic achievement. A descriptive qualitative approach was employed, combining a literature review and documentation analysis. Data sources included BOS Kinerja reports from 2022-2024, school learning evaluation records, and relevant academic literature. Thematic content analysis was used to interpret the data. The findings reveal that BOS Kinerja funds were primarily allocated for teacher training in Higher-Order Thinking Skills (HOTS), strengthening formative assessment, procuring digital learning tools, and developing project-based and differentiated learning models. These initiatives contributed to improved teacher competence, increased student participation, better academic performance, and reduced absenteeism. However, several challenges persist, such as limited managerial human resources, weak monitoring from local education authorities, and the absence of inter-school evaluation forums. The study recommends strengthening school leadership and managerial capacity, implementing systematic and collaborative evaluation mechanisms, and fostering cross-school collaboration to maximize the long term benefits of BOS Kinerja.